Authoritative vs. Participative leadership communication: Shaping academic careers in Islamic higher education - Kompri, Kompri; Nadiyah, Nadiyah; Rohim, Fahmi; Kaharuddin, Kaharuddin; Maulana, Maulana (Universitas Jambi, Indonesia, 2026)
This study explores the role of leadership communication patterns—authoritative and participative—in shaping the academic career development of lecturers at Islamic higher education institutions in Jambi Province, Indonesia. Using a qualitative case study approach, data were collected through in-depth interviews and document analysis involving lecturers from multiple institutions. The findings reveal that participative leadership communication fosters motivation, job satisfaction, and career progression through open dialogue, mutual respect, and collaborative decision-making. In contrast, authoritative communication tends to limit professional growth and reduce engagement. The study emphasizes that leadership style significantly influences lecturers' loyalty, innovation, and academic productivity. These findings highlight the importance of adopting inclusive communication strategies to support human resource development in Islamic universities. The study contributes to the discourse on leadership in faith-based education settings. It offers practical recommendations for institutional leaders to enhance career pathways through more responsive and participative leadership practices.